In War Time: Whittier's Civil War Address and The Quaker Periodical Press. Issue 2 (December 2015) - High, Ean
Abstract : Fought, at least in part, for a cause in which many Quakers ostensibly believed and had previously risked a great deal for, the American Civil War was a time of great trial for American Quakers. Extending ongoing efforts to understand this complex period, the following essay considers John G. Whittier's mid-war poem, 'In War Time', and the peculiarity of its simultaneous appearance in the major Hicksite, Gurneyite and Wilburite periodicals of the nineteenth century. Consequent of the singularity of its shared printing, Whittier's poem renders more legible the dilemma Friends faced when attempting to position their peace principles in ethical relation to the mass suffering of the war. Reflecting, while also contributing to, a major transformation in American Quakerism, 'In War Time' questioned the ethics of dissociative pacifism, exhorting members of the Society to assist the Union war effort, if only in noncombatant roles, as nurses in hospitals and as teachers among the freedmen.